Ruskijat tăkač. Petăr Alekseevič Alekseev. [... Săs sătrud na] F. Volchovski [F.(V.) Volchovskij] i Verbovčanin [Psev. na S.S. Sinegub]. Perv. ot ruski G.B. [= G.I. Bakalov] (Bakalov, 1901)
(III chiljada).